ANALISIS FINANCIAL DISTRESS STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Sitanggang, Abdonsius (Jurnal Manajemen dan Bisnis, 2013)
The research aims to analyze the financial conditions to assess financial health at a manufacturing company in Indonesia Stock Exchange Listings. The benefits of the research is to provide material information to management and stakeholders regarding financial health as a material consideration for management or other parties, such as investors and potential investors, creditors and other parties for decision making. The population of the research was the financial report of a manufacturing company in Indonesia stock exchange listing as many as 140 companies. Sample research is as many as 30 companies. Opersionalisasi research is variable: the ratio of working capital to Total Assets, the ratio of net income to Total Assets was detained, the ratio of EBIT to Total Assets, and the ratio of the value of the capital markets themselves by taking action against Total Debt in 2009-2011. The required data are secondary data collected through technical documentation, data analysis techniques used are descriptive method. Based on the results of the study it can be concluded that corporate financial kondish manufacturing Indonesia stock exchange listings are rated from financial ratios, that ratio analysis is not membarikan a clear picture to stakeholders about health conditions and symptoms of the bankruptcy of the company. The listhne manufacturing company in BEI has not used the Z-Score model to know their financial health. Sporting results results of the discriminant equation obtained data 0, 553X1 0, 507X2 0, 409X3 0, 009X4. The value of the discriminant tells us that the ratio of working capital to Total Assets, the ratio of net income to Total Assets was detained, the ratio of EBIT to Total Assets and the ratio of the value of Own capital market Debt to Total positive effect of bankruptcy prediction manufacturing company listed in the stock exchange Inonesia. Wilks Lambda test results show that the ratio of working capital to Total Assets Ratio Return on hold, with a Total Assets, the ratio of EBIT to Total assets and market value of private equity with Total debt, significant positive effect on the symptoms of a manufacturing company in bankruptcy listings in Indonesia stock exchange. The z-score of 2009 indicates that its financial condition healthy companies as much as 22 companies and there are 8 companies in financial distress, indicating conditions are forecast to be bankrupt. In 2010, there were 21 companies that have a healthy financial condition while nine companies in In 2011, there are 24 companies that have a healthy financial condition while 6 company again in conditions of financial distress which indicates the forecast will go bankrupt. The advice given as consideration to the company is the company should implement a Z-Score method for knowing the financial condition, whether in financial distress or in kodisi healthy so that management and the users of the financial statements and other information to assess and predict the likelihood of the presence of symptoms of the bankruptcy of the company